Grassi, M. (2023). Phármakon: desalojos del deseo y la escritura. Sb Editorial, 160 pp. ISBN 978-631-6503-73-2 - Jamsinoy, Marcos (2025)
Fil: Jamsinoy, Marcos. Academia Nacional de Ciencias; Argentina